Maternal postpartum anxiety and the development of infant attachment: the effect of body sensations on infant attachment - Klauser, Nathania; Müller, Mitho; Zietlow, Anna-Lena; Nonnenmacher, Nora; Woll, Christian; Becker-Stoll, Fabienne; Reck, Corinna (Journal of affective disorders, 2023)
Background - Knowledge about the influences of maternal postpartum anxiety disorders (PAD) on infant development is limited. Aim of this present study is to evaluate the influence of PAD on infant attachment. - Methods - In a longitudinal study, self-reported anxiety symptoms of N = 70 mothers (N = 28 with PAD diagnosed according to the DSM-IV, N = 42 controls) were examined in the postpartum period and one year later. Infants' attachment was observed in the Strange Situation Test (SST) at the age of 12-24 months. - Results - Results indicate a strong relationship between PAD and infant attachment: infants of mothers with PAD were significantly more likely to be classified as insecure or disorganized than infants of control mothers. Logistic regression analysis led to a significant model with 76.8 % correct classification of infant attachment dependent on the maternal fear of anxiety associated body sensations (OR = 4.848) in the postpartum period. Including maternal sensitivity and interaction behavior, only maternal intrusiveness was additionally associated with infant attachment (ρ = 0.273, p < .05; OR = 45.021, p = .153). - Limitations - Participants were highly educated. Different anxiety disorders included led to a heterogenous sample. Generalization is diminished. Maternal sensitivity was measured on a global scale, and body tension was self-reported. - Conclusions - PAD plays a crucial role in the development of infant attachment. Interaction-focused interventions, helping mothers to decrease intrusiveness, and body-focused interventions, helping mothers to deal with their fear of anxiety symptoms, might be promising pathways to buffer the influence of PAD on infant attachment.